Discursive Incivility in Geopolitical Conflict: A Cognitive-Linguistic Analysis of Trump’s Discourse - Abdelhafeez, Mostafa; Gabeen, Mahmoud Ali (Journal of Posthumanism, 2025)
This study examines the discursive strategies and conceptual metaphors underpinning incivility in Donald Trump's geopolitical rhetoric, focusing on his discourse targeting China, GCC states, and Russia, among other nations. Through Critical Discourse Analysis (CDA) and Conceptual Metaphor Theory (CMT), a corpus of speeches and tweets during the two Trumpian terms of U.S. presidency is analyzed to identify three recurrent patterns: (1) dehumanizing metaphors (e.g., framing China as a "virus"), (2) transactional framing of alliances (e.g., framing GCC states as "freeloaders"), and (3) adversarial hyperbole (e.g., framing relations with Russia as a "hoax"). The analysis reveals how these cognitive-linguistic patterns weaponized incivility to reconstruct diplomacy as zero-sum conflict, reinforcing moral dichotomies (us vs. them). By systematizing the interplay between metaphor, toxic discourse, and geopolitical othering, this study contributes to political linguistics literature while offering an analytical framework for understanding populist rhetoric's role in international relations.